Jamaah Tabligh Cot Goh: Historis, Aktivitas dan Respon Masyarakat - Husaini Husda (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2017)
This paper explores the basic matters related to the reason Tabligh Jamaah chose Cot Goh Mosque asa center of activity in Aceh; history and activities of Jamaah Tablihg in Cot Goh and the community’s response inthis region to the existence of Jamaah Tabligh in Cot Goh. This paper is the result of research using qualitativeapproach through naturalistic method. The data were collected by observation, interview and decumentationanalysis. Based on existing data, Jamaah Tabligh as an Islamic reform movement that chose the path of culturaldakwah originating from Mehwat North India has managed to spread to all corners of the world. To Indonesia,this movement has also managed to get into all corners of the country. This movement in Aceh is centered in CotGoh Mosque which is located in Gampong Lamme Garot Sub Montasik Aceh Besar. The choosing of this placeis caused by the central figure of Jamaah Tabligh Ustad Razi bin Raden Sulaiman is from this region, making iteasier for the organization to build communication with the surrounding community. Jamaah Tabligh is doinga variety of religious activities are very positive with various activities of dakwah, memakumrkan mosque, re-membrance and prayer, giving pronunciation salam, civilize the language of religion in every activity. The com-munity response around Cot Goh to Jamaah Tabligh is very positive by supporting and following all the activities.